Effects of Exercise Interventions for Type 2 Diabetes patients: a meta-analysis of randomized controlled trials (Bangladesh Journal of Medical Science, 2025)
Objective To evaluate the effects of exercise interventions on HbA1C, fasting blood glucose (FBG), lipid profiles, blood pressure, anthropometric components, insulin, Homeostasis Model Assessment for Insulin Resistance (HOMA-IR), and inflammatory markers among type 2 diabetes patients. Methods We conducted a meta-analysis of randomized control trials (RCTs). Seven electronic databases, namely CINAHL, the Cochrane Library, Embase, Ovid-Medline, PubMed, Scopus, and Web of Science were searched from inception to September 12, 2022 to identify RCTs assessing the effects of exercise for type 2 diabetes. Hedges’ g and 95% confidence interval (CI) were calculated as the pooled estimates using a random-effects model, and a two-sided P of